Sinus balloon technic for treatment of malar bone fractures - MAKINO, Shinya; KAWAI, Tsuyoshi; IIDA, Susumu; SHIMOZATO, Kazuo; KANOH, Yoshinori; OHIWA, Ichiro (Japanese Journal of Oral and Maxillofacial Surgery, 1987)
Sinus balloon technique for reduction of 27 malar bone fractures was utilized and good results were obtained. We reported the outlines of the technique. The procedure was as follows: 1. The fracture line of zygomatico-frontal sutures was settled by φ0.6mm wire. 2. The fractured area was certified and the insertion of a Foley balloon catheter was performed using a vestibular approach. The balloon was inflated using 16-20 ml of normal saline solution. This procedure thus resulted in satisfactory reduction of the fractures. Operation time was approximately 1 hour. 3. The volume of normal saline solution was decreased a few ml at a time over 1 to 2 weeks. The balloon was then removed. The Sinus balloon technique is a very useful treatment for malar bone fractures in view of simplifing the operation, shortening time, and reducing postoperative complications.